(-12)=3x(-4)

Simple and best practice solution for (-12)=3x(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-12)=3x(-4) equation:


Simplifying
(-12) = 3x(-4)
-12 = 3x(-4)

Reorder the terms for easier multiplication:
-12 = 3 * -4x

Multiply 3 * -4
-12 = -12x

Solving
-12 = -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-12 + 12x = -12x + 12x

Combine like terms: -12x + 12x = 0
-12 + 12x = 0

Add '12' to each side of the equation.
-12 + 12 + 12x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 12x = 0 + 12
12x = 0 + 12

Combine like terms: 0 + 12 = 12
12x = 12

Divide each side by '12'.
x = 1

Simplifying
x = 1

See similar equations:

| Indv/v^2-v | | 1/3x-15=x | | 3x(4-1)+7=25 | | 8a+9=3a+1 | | (2x-2y)-12=0 | | 0.06*x=0.43 | | 2-4(-6x+2)=-3x | | 108-14x=2x+24 | | 2-3(-7x-1)=-5(-x-7)+8 | | 2-3(-7x-1)=-5(-x-7) | | 14-6x=7-9x | | 225434.43x=381718(0.3193927+x) | | 32+6x*5=0 | | 32+5*5=0 | | 40y=16x-15 | | 3x(x^2+3x+2)=0 | | 0.1y+0.8=0.1-0.6y | | 3x+15=56-3x | | (X-3)(x+3)=14 | | 5(m+3)=2mb+24 | | 2x^2-585x+1000=0 | | X-4x+8x-7x-5x=9-2-8 | | 2x^2-585+1000=0 | | 24x-2y=-1 | | X+8-4x+8x=7x+9+5x-2 | | 9-(1-3y)=48+y-(3-y) | | 2x-5/-45/4 | | x^2+7*x+29=0 | | (8x+5)-20x=x | | -5(2/3)=(2/3)-6(2/3)= | | -5*2/3= | | 2y-6+3x=0 |

Equations solver categories